AT-TA’ĀWUN ROKḻZAH LI AL-HAYĀH: DIRĀSAH TAHLḻLIYAH LI AL-MATṠAL AL-ARABY - Tajudeen Yusuf (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Many Arabic proverbs emphasize the importance of collaboration and its influence on the progress and development of humans and society. This study chooses proverbs as the object of study because of their wide distribution and universality. This paper aims to study the Arabic proverb al-yadu al-wahidah la tushaffiq, which gives advice about human life, experience, and many lessons. It discusses the various forms of human collaboration in society. This paper is qualitative descriptive research. The data collection technique in this research is the documentation technique. As for the data analysis technique used, it includes reading, categorization, and interpretation, as well as concluding. This research shows that al-yadu al-wahidah la tushaffiq proverb shows the importance of cooperation between human beings. Humanity is complete and can only progress with collaboration and teamwork. Al-yadu al-wahidah la tushaffiq proverb shows that collaboration can take various forms: community cooperation, security cooperation, peace cooperation, and economic cooperation